Correlates of Successful Enrollment of Same-Sex Male Couples Into a Web-Based HIV Prevention Research Study: Cross-Sectional Study - Stephenson, Rob; Chavanduka, Tanaka MD; Sullivan, Stephen; Mitchell, Jason W (JMIR Publications, 2020)
BackgroundThe recognition of the role of primary partners in HIV transmission has led to a growth in dyadic-focused HIV prevention efforts. The increasing focus on male couples in HIV research has been paralleled by an increase in the development of interventions aimed at reducing HIV risk behaviors among male couples. The ability to accurately assess the efficacy of these interventions rests on the ability to successfully enroll couples into HIV prevention research. ObjectiveThis study aimed to explore factors associated with successful dyadic engagement in Web-based HIV prevention research using recruitment and enrollment data from a large sample of same-sex male couples recruited online from the United States. MethodsData came from a large convenience sample of same-sex male couples in the United States, who were recruited through social media venues for a Web-based, mixed method HIV prevention research study. The analysis examined the demographic factors associated with successful dyadic engagement in research, measured as both members of the dyad meeting eligibility criteria, consenting for the study, and completing all study processes. ResultsAdvertisements generated 221,258 impressions, resulting in 4589 clicks. Of the 4589 clicks, 3826 individuals were assessed for eligibility, of which 1076 individuals (538/1913, 28.12% couples) met eligibility criteria and were included in the study. Of the remaining 2740 ineligible participants, 1293/3826 (33.80%) were unlinked because their partner did not screen for eligibility, 48/2740 (1.75%) had incomplete partner data because at least one partner did not finish the survey, 22/2740 (0.80%) were ineligible because of 1 partner not meeting the eligibility criteria. Furthermore, 492/3826 (12.86%) individuals were fraudulent. The likelihood of being in a matched couple varied significantly by race and ethnicity, region, and relationship type. Men from the Midwest were less likely to have a partner who did not complete the survey. Men with college education and those who labeled their relationships as husband or other (vs boyfriend) were more likely to have a partner who did not complete the survey. ConclusionsThe processes used allowed couples to independently progress through the stages necessary to enroll in the research study, while limiting opportunities for coercion, and resulted in a large sample with relative diversity in demographic characteristics. The results underscore the need for additional considerations when recruiting and enrolling, relative to improving the methods associated with these research processes.